ANALISIS KANDUNGAN PROTEIN KASAR DAN SERAT KASAR PADA LIMBAH SAYURAN PASAR (KOL, SAWI, KULIT JAGUNG) DENGAN PENAMBAHAN EM4 SEBAGAI PAKAN ALTERNATIF: Analysis of Crude Protein and Crude fiber Content in Market Vegetable Waste (Cabbage, Mustard, Corn Skin) with the Addition of EM4 as Alternative Feed) (Buletin Nutrisi dan Makanan Ternak, 2022)
Vegetable waste can be used as ruminant animal feed because it is abundantly available and has economic value, the price is cheap and does not compete with human needs, besides that it can reduce environmental pollution. The purpose of this study was to determine the content of crude protein and crude fiber in market vegetable waste as an alternative feed with the addition of EM4. This study used a completely randomized design (CRD) method which consisted of 4 treatments and 3 replications. The results of this study were the addition of EM4 and molasses gave a very significant effect (P